2021
DOI: 10.1016/j.redox.2021.102060
|View full text |Cite
|
Sign up to set email alerts
|

Alpha1-antitrypsin counteracts heme-induced endothelial cell inflammatory activation, autophagy dysfunction and death

Abstract: Free heme toxicity in the vascular endothelium is critical for the pathogenesis of hemolytic disorders including sickle cell disease. In the current study, it is demonstrated that human alpha1-antitrypsin (A1AT), a serine protease inhibitor with high binding-affinity for heme, rescues endothelial cell (EC) injury caused by free heme. A1AT provided endothelial protection against free heme toxicity via a pathway that differs from human serum albumin and hemopexin, two prototypical heme-binding proteins. A1AT inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…However, plasma albumin levels in severe septic patients also decrease when compared to those in non-septic patients ( 54 ). We and other researchers have shown that AAT, similarly to albumin, binds free heme and neutralizes its cytotoxic effects ( 11 , 55 , 56 ). In this study, we demonstrate that a strong accumulation of free heme in the peritoneal cavity of septic mice was significantly reduced by AAT treatment.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…However, plasma albumin levels in severe septic patients also decrease when compared to those in non-septic patients ( 54 ). We and other researchers have shown that AAT, similarly to albumin, binds free heme and neutralizes its cytotoxic effects ( 11 , 55 , 56 ). In this study, we demonstrate that a strong accumulation of free heme in the peritoneal cavity of septic mice was significantly reduced by AAT treatment.…”
Section: Discussionmentioning
confidence: 78%
“…It is important to point out that AAT not only interacts with target proteases and inhibits their activity but also binds and neutralizes various inflammatory substances such as free radicals, chemokines [interleukin 8 (CXCL8) and leukotriene B4 (LTB4)], cytokines [tumor necrosis factor (TNF)], and complement factors. Like albumin, AAT also interacts with free heme and neutralizes its toxicity ( 10 , 11 ). The fact that the half-life of circulating AAT is prolonged during bacteremia suggests that AAT is an important protection against organ damage ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Heme, a typical damage-associated molecular pattern (DAMP), recognizes receptors through patterns such as Toll-like receptors, induces autoimmune or immune tolerance, and plays an important role in the development of inflammation. [7][8][9][10] Heme can induce lipid peroxidation and mediate TNF-α-mediated programmed cell death. 11 In endothelial cells, heme not only activates NLRP3 inflammatory bodies, leading to inflammation but also induces endothelial barrier disturbance through the MKK3/p38MAPK axis, leading to impaired lung function.…”
Section: Introductionmentioning
confidence: 99%
“…AAT also interacts with chemoattractants, such as IL-8 and leukotriene B4 (LTB4), and thus modulates neutrophil adhesion and chemotaxis (Mcelvaney et al, 2020). The interaction between AAT and free heme neutralizes the cytotoxic effects of heme (Madyaningrana et al, 2021). These various interactions between AAT and its binding partners might dependent on the glycosylation and/or the hydrophilic/hydrophobic surface charges of the AAT (Mcelvaney et al, 2020).…”
Section: Introductionmentioning
confidence: 99%